Helping EGFR inhibition to block cancer - Warta, Rolf; Herold-Mende, Christel (Nature neuroscience, 2017)
Effectiveness of EGFR treatment is impaired through an early adaptive response. TNF-JNK-Axl-ERK signaling contributes to this primary resistance to EGFR inhibition and might serve as novel target to improve EGFR inhibition.
Gesehen am 28.11.2018